S56 The impact of azithromycin in idiopathic pulmonary fibrosis. (15th November 2017) - Alzaher, O; Macaluso, C; Maritano, J; Chaube, R; Chua, F; Kokosi, M; Kouranos, V; Wells, AU; Maher, TM; George, PM; Renzoni, ER; Molyneaux, PL
Abstract : Introduction: There is growing evidence of the role of infection in the pathogenesis of Idiopathic pulmonary fibrosis (IPF). Azithromycin, a macrolide antibiotic, has antibacterial and anti-inflammatory activity and has shown to be beneficial in animal models of lung fibrosis. This study aimed to assess the effects of prophylactic Azithromycin on hospital admissions, rescue antibiotic use and lung function in IPF. Method: A retrospective analysis identified all IPF patients receiving a prophylactic prescription of 250 mg Azithromycin three times a week (Monday, Wednesday and Friday) between 2012 and 2017. An IPF diagnosis was made, according to international guidelines, 1 following multi-disciplinary team discussion. The use of immunosuppressive therapy, immunodeficiency or the use of other prophylactic antibiotics resulted in study exclusion. Results: One hundred and fifteen patients with IPF receiving prophylactic Azithromycin were identified. Thirteen already established on therapy and 5 who received other prophylactic antibiotics were excluded. The remaining 97 IPF subjects had a mean age of 66.05±11.25 years, were predominantly male (65%) with moderately severe disease (DLco 34%±9.5% predicted; FVC 70%±18% predicted). The majority (92%) of IPF patients tolerated Azithromycin, only 8 (8.25%) discontinued therapy due to side effects (tinnitus (n=1) and gastrointestinal intolerance (n=7)). One discontinued following lung transplant and 4 had therapy discontinued at the discretion of the prescribing clinician who felt there had been no subjective improvement. In the Pre-treatment twelve month period a total of 29 hospital admissions (0.30±06 per patient years) and 146 courses of antibiotics (1.50±1.70 per patient years) were recorded. In the same cohort a year after commencing prophylactic Azithromycin, there were 7 hospital admissions (0.08±0.3 per patient years) and 31 therapeutic antibiotic courses prescribed (0.36±0.8 per patient years) (p=0.0086, p<0.0001 respectively) (figure 1 ). Lung function rate of change over the 12 months preceding and following initiation of antibiotics was examined and there was no significant change in rate of decline in either FVC or DLco. Conclusions: The present study has shown the beneficial effect of prophylactic Azithromycin in IPF patients, decreasing both hospital admissions and antibiotic usage, however, further randomised placebo controlled studies are needed to support and confirm our findings. Reference: Raghu G, Collard HR, Egan JJ, et al . An official ATS/ERS/JRS/ALAT statement: idiopathic pulmonary fibrosis: evidence-based guidelines for diagnosis and management. Am J Respir Crit Care Med 2011;183:788824.